Analisis Perbandingan Kinerja Dan Risiko Portofolio Optimal Saham Kompas 100 Menggunakan Single Index Model Dan Capital Asset Pricing Model Periode 2020-2023 - Riwu, Yonas Ferdinand; Natonis, Sari Angriany; Kamuri, Klaasvakumok J.; Faah, Yuri Sandra; Manongga, Irience R. A. (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
The LQ-45 stock index is a reference for investors on the Indonesia Stock Exchange (BEI) because it consists of industries with large liquidity and makes it easier for investors to sort some shares but represents the total stock market performance. The purpose of this study was to determine the differences in performance and optimal risk of the Single Index Model (SIM) and Capital Asset Pricing Model (CAPM) portfolios for the period August 2020 – January 2023. This research is a descriptive study with a quantitative approach. The data collection technique used is a documentation study. Based on the calculation results, it is found that there are differences in MIS portfolio returns to CAPM, there is no difference in MIS portfolio risk to CAPM, there are differences in MIS portfolio performance evaluated using the Sharpe, Treynor and Jansen methods and no differences in CAPM portfolio performance evaluated using the Sharpe, Treynor method, and Jensen.